Unusual complication of bladder catheterization in child: catheterization of ureter - Sekmenli, Tamer; Ciftci, Ilhan (Prague Medical Report, 2015)
Bladder probing is an invasive procedure that is often used by paediatric and other surgeons. We present a case who was ureter catheterized accidentally while placing a probe into the right ureter in an 18 months old female. If different catheter localization is determined during the examination, the process must be terminated immediately and the relevant specialist should be informed right away.
Keywords: Ureter; katetrizace močového měchýře; ureter; Humans; lidé; Female; Unnecessary Procedures; Infant; Urinary Catheterization; Urography; Vesico-Ureteral Reflux; kojenec; procedury zbytečné; vezikoureterální reflux; ženské pohlaví; urografie